Pengaruh waktu simpan Packed Red Cells (PRC) terhadap perubahan kadar hemoglobin, hematokrit, dan glukosa plasma di RSUP H. Adam Malik, Medan, Indonesia - Pesalmen Saragih; Ida Adhayanti; Zulfikar Lubis; Herman Hariman (DiscoverSys Inc., 2019)
Background: Someone who approves the PRC must have been transfused no more than 24 hours after the creation of the PRC; some also apply 3 days. But there are also those that apply up to 1 week. PRC is still feasible to be transfused immediately by seeing changes that occur in the value of hemoglobin (Hb), hematocrit (Ht), and plasma needed when storing.Methods: 30 whole blood bags (WB) were taken for this study. The WB is at the request of the doctor for the manufacture of PRC. The blood bag is rotated at a speed of 4,000 RPM for 15 minutes. From the PRC, 3 cc of blood was taken on 1,3,5,7 days for hemoglobin (Hb), hematocrit (Ht), and glucose plasma. Data were analyzed using SPSS version 21 software for Windows.Results: After 1-day taking 3 cc of blood, PRC was stored at 4 Â° C, and then 3cc was taken also on days 3, 5, 7. The results showed that hemoglobin (Hb), hematocrit (Ht) increased from day 1 until day 7 but not significant (P> 0.05), plasma plasma showed a decrease from day 1 to day 7 and significant (P <0.001) but the value was still within normal limits. Correlation value between Hb and PRC retention time; r = 0.127, Ht with the shelf life of PRC, r = 0.160, plasma glucose with the length of time the PRC is stored; r = -0,844.Conclusion: PRC stored for 7 days is still feasible to use. There was a decrease in plasma glucose but still within normal limits.